2017
DOI: 10.3382/ps/pex035
|View full text |Cite
|
Sign up to set email alerts
|

Straight-run vs. sex separate rearing for 2 broiler genetic lines Part 1: Live production parameters, carcass yield, and feeding behavior

Abstract: The objective of this experiment was to evaluate the effects of raising broilers under sex separate and straight-run conditions for 2 broiler strains. Day-old Ross 308 and Ross 708 chicks (n = 1,344) were separated by sex and placed in 48 pens according to the rearing type: sex separate (28 males or 28 females) or straight-run (14 males + 14 females). There were 3 dietary phases: starter (zero to 17 d), grower (17 to 32 d), and finisher (32 to 48 d). Birds' individual BW and feed intakes were measured at 12, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
2
16
1
7
Order By: Relevance
“…There was a significant interaction (p<.005) among the factors for the variables WG and FI, in which the French, Hubbard and Cobb showed greater homogeneity between males and females, differently from Ross in which the males presented greater weight gain in the first week when compared to the females. Similar result to Da Costa et al (2017) was found when evaluating the performance of the Ross strain in mixed or single sex, the males had higher WG than females. The results observed in the WG are justified by the increase in the FI of the birds, i.e., birds with higher FI showed higher WG, justifying the absence of significant results (p>.005) for the FC variable.…”
Section: Resultssupporting
confidence: 82%
“…There was a significant interaction (p<.005) among the factors for the variables WG and FI, in which the French, Hubbard and Cobb showed greater homogeneity between males and females, differently from Ross in which the males presented greater weight gain in the first week when compared to the females. Similar result to Da Costa et al (2017) was found when evaluating the performance of the Ross strain in mixed or single sex, the males had higher WG than females. The results observed in the WG are justified by the increase in the FI of the birds, i.e., birds with higher FI showed higher WG, justifying the absence of significant results (p>.005) for the FC variable.…”
Section: Resultssupporting
confidence: 82%
“…Wide variations in amino acid digestibility have been reported in animal source proteins, particularly in terms of batch-to-batch differences [ 34 ]. The differences in responses to Arg or Val addition may be due to the difference in dietary protein sources, inclusion levels and amino acid requirements for broiler males and females [ 35 , 36 , 37 , 38 ]. It has been suggested that the protein and/or amino acid levels of the diets, strain, and the age of the birds may affect the response to the level of amino acid addition [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Por meio das médias apresentadas na Figura 1, verifica-se que o fator de produção obtido em aviários em que foram alojados somente machos (FP = 323,93) foi 18% superior ao apresentado em instalações exclusivas de fêmeas (FP = 274,61) e 6,7% maior que em galpões com aves não sexadas (FP = 303,71). Gottardi et al (2019), Api et al (2017), Da Costa et al (2017 e Martins et al (2012), em avaliações de produtividade associadas à separação das aves de acordo com seus gêneros, também constataram que lotes exclusivos de machos apresentaram melhores indicadores zootécnicos que lotes de aves não sexadas (mistas) e lotes de fêmeas.…”
Section: Resultsunclassified
“…Estudos sobre desempenho produtivo de frangos de corte, de acordo com a linhagem e o gênero, indicam que os resultados zootécnicos da criação exclusiva de machos são melhores que os obtidos em galpões de aves não sexadas e de fêmeas (GOTTARDI et al, 2019;API et al, 2017e MARTINS et al, 2012. Além destas constatações, Da Costa et al (2017) ainda observaram que a produção mista (sem separação das aves de acordo com o sexo) favoreceu machos e prejudicou fêmeas em comparação com criações exclusivas para cada um desses gêneros.…”
Section: Panorama Sobre Análises Econômicas E Zootécnicas Na Produção De Frangos De Corteunclassified